Microstructure, defects, and mechanical properties of wire + arc additively manufactured AlCu4.3-Mg1.5 alloy - Gu, Jianglong; Gao, Minjie; Yang, Shouliang; Bai, Jing; Zhai, Yuchun; Ding, Jialuo (Elsevier, 2019)
The wire with a composition of AlCu4.3%Mg1.5% was customized and used to deposit the WAAM alloy with the power source of cold metal transfer. The microstructure, defect, and mechanical properties of the as-deposited and heat-treated WAAM alloys were studied. Key findings demonstrated that the microstructure of the as-deposited alloy was characterized by a hierarchical distribution of dendrites, equiaxed grains, and a slight number of columnar grains. The volume fraction of the network-like scattered coarse particles of second phases θ + S reduced by 95% after the T6 heat treatment. With an average microhardness of 161.4 HV, the mean yield strength and ultimate tensile strength of the WAAM alloy increased by 116% and 66% achieving 399 MPa and 485 MPa in the horizontal direction after heat treatment. The precipitation of a high density of needle-shaped metastable S′ precipitates was responsible for the significantly enhanced mechanical properties. However, this WAAM alloy has exhibited an anisotropic tensile property. A considerable number of sharp-angled defects like linear and chain-like micropores, which generally depress the mechanical properties, were formed in the WAAM alloys.
Keywords: Wire + arc additive manufacturing; Al alloy; Al-Cu-Mg; Microstructure; Defect; Mechanical property